(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
The research tackled one of the important housing problems in Iraq, which is the problem of affordable housing, by identifying the real housing need in the target year in the year 2030, as the year 2019 was adopted as the base year. The importance of this came as a result of the disparity of statistics about the real number required of housing units. Also the research focused on the importance of the anchor of the social factor in the comfort and reassurance of the residents, and not the economic anchor exclusively, as is common in affordable housing projects, as this approach resulted in the research problem: The existence of a knowledge gap in the non-response of housing complexes to middle and low societal segments of the basis of the social factor for affordable housing in multi-housing units in Iraq, where a group of vocabulary and indicators of affordable housing was identified in the field of the influence of the social factor and that through the literature and studies cited by the research .The basic vocabulary and secondary indicators of social factor were applied to local and regional experiences Where the local experience in the new city of Bismayah has produced good results that can be taken in the future in the field of affordable housing, especially the impact of the social factor on the comfort and reassurance of the residents. Affordable housing for young families.